Virtual reality technologies in a dynamic change of human resources management - Herlin Widasiwi Setianingrum; Bisri Bisri; Tri Widyastuti; Safrezi Fitra (Institute of Computer Science (IOCS), 2023)
The purpose of this review is to see how technology crosses paths with human management needs. We can call it human resources (HR) technology solutions, software and hardware solutions that can automate HR processes, collect, process, and analyse data, use it to make strategic decisions, and perform HR professional work and operations with security and privacy in mind. This research method is a literature review that is carefully elaborated in the form of qualitative descriptions. The results of the study found that Digital Transformation and new technologies have started to be used in HR processes. Both HR professionals and other stakeholders have been in HR processes using these technologies. In this study, we evaluate how Artificial Intelligence, Virtual Reality and Metaverse, which are the current trending technologies, are used in HR management. We also emphasise on potential opportunities and new use cases.